Platform for Action / and the Beijing Declaration - United Nations (New York, NY, 1996)
Translating the Momentum of Beijing into Action, Beijing Declaration, Platform for Action, Mission Statement, Global Framework, Critical Areas of Concern, Strategic Objectives and Actions, Institutional Arrangements, Financial Arrangements.